Effectiveness of Educational Intervention Regarding Polycystic Ovarian Syndrome Among Undergraduate Students of Tanahu - Shrestha, Remana; Darshandhari, Gayetri (Journal of Karnali Academy of Health Sciences, 2024)
Background: Polycystic Ovarian Syndrome (PCOS) is a new emerging complex endocrine disorder affecting a significant number of women worldwide, characterized by hormonal imbalances, reproductive irregularities, and metabolic disturbances. The overall objective was to find out effectiveness of the educational intervention on knowledge on polycystic ovarian syndrome among undergraduate students. Methods: This true experimental study design was carried out in a selected campus of Tanahun district. The study population was undergraduate students who were 18 years and above. A systematic random sampling technique was adopted to select the sample. Data was collected by a pre-tested self-administered questionnaire before educational intervention. The questionnaire was developed by the researcher herself/himself through consulting subject experts and searching literature. The educational intervention package was developed. After three weeks of intervention, a posttest was conducted. The data was entered on SPSS 21.0 version and the result was analyzed by using descriptive statistics and inferential statistics. Results: The knowledge levels of respondents before and after the intervention, along with a control group show that in the pre-intervention phase, a substantial majority of students (96.6%) had an unsatisfactory knowledge level, while only 3.4% fell into the satisfactory category. Following the intervention, with 100% of students achieving a satisfactory knowledge level. In the control group there is a maintained high percentage of unsatisfactory knowledge pre-intervention (98.3%), with a marginal decrease to 96.6% post-intervention. In a study the intervention group showed a significant increase in knowledge with a median pretest score of 3 rising to 28 posttest. Their change score of 25 was highly significant (p=0.00). The control group had a smaller increase from a pretest score of 0 to 2 posttest, with a change score of 2 and a significant p value indicating the intervention’s effectiveness. Conclusion: The positive outcomes observed in this study underscore the importance of an educational initiative in the broader context of health education for young adults.